Reducing Outpatient Opiate Utilization in the Postpartum Period [32E]. (May 2020) - Conroy, Meredith; Altman, Alan; Marcotte, Michael Paul; Mincarelli, Delores; Holbert, Michael; Crisp, Catrina C.
Abstract : INTRODUCTION: The United States is experiencing an epidemic of opiate-related deaths with rates continuing to rise. The majority of postpartum women use only half of opioid tablets prescribed at discharge, and 95% of women do not dispose of excess medication by the postpartum visit. This offers an opportunity to modify physician prescribing habits during the postpartum period. METHODS: This is an IRB approved retrospective study at a single, high-volume tertiary healthcare system over four years from January 1, 2015, to December 31, 2018. Women were excluded if they received methadone or buprenorphine during the inpatient postpartum period. The primary outcome was morphine milligram equivalents (MME) prescribed at discharge and within 21 days of discharge. RESULTS: Among vaginal deliveries, there was a significant reduction in prescribed MME from 109.4 mg in 2015 to 5.5 mg in 2018 ( P <.0001), with an increase in the percentage of patients with no opioids prescribed at discharge or in the immediate postpartum period from 29.5% in 2015 to 93.1% in 2018 ( P <.0001, OR 32.3 CI 22.2–41.0). Among cesarean deliveries, there was a reduction in prescribed MME from 235.8 mg in 2015 to 152.6 mg in 2018 ( P <.0001), with a decrease in the percentage of patients with no opioids prescribed at discharge or in the immediate postpartum period from 20.0% to 15.5% ( P =<.02, OR 0.73 CI 0.57–0.96). CONCLUSION: A change in physician prescribing habits can significantly reduce opiate utilization in the postpartum period.